2014
DOI: 10.1177/156482651403500304
|View full text |Cite
|
Sign up to set email alerts
|

Community Development and Livestock Promotion in Rural Nepal: Effects on Child Growth and Health

Abstract: Heifer interventions resulted in improved socioeconomic status and household income per family member. Children under 60 months of age in the intervention group had greater incremental improvement in height-for-age and weight-for-age z-scores than children in the control group, and longer participation in Heifer activities was associated with better growth. Poverty alleviation programs, such as Heifer, may indirectly benefit child growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 17 publications
3
36
0
Order By: Relevance
“…Therefore, food and nutrition security programs could benefit hugely from applying a socioanthropological lens in their design and implementation, in a context-specific manner. Interventions aiming at producing ASF for nutrition security should include a 'Social and Behaviour Change Communication' (SBCC) strategy to promote their uptake at the dietary level (or alternatively to trade them for other nutritious food groups) (Miller et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, food and nutrition security programs could benefit hugely from applying a socioanthropological lens in their design and implementation, in a context-specific manner. Interventions aiming at producing ASF for nutrition security should include a 'Social and Behaviour Change Communication' (SBCC) strategy to promote their uptake at the dietary level (or alternatively to trade them for other nutritious food groups) (Miller et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, bad practices (poor preservation or inappropriate handling of ASF) were indicated to lead to food safety, health and nutritional problems. Understanding specific practices, enhancing and hindering drivers (including gender and taboos for ASF consumption) were considered essential to the successful design and implementation of a nutrition-sensitive livestock intervention (Meyer-Rochow 2009;Miller et al 2014). Also, food safety in relation to ASF and nutrition was identified as an area with important evidence gaps.…”
Section: Resultsmentioning
confidence: 99%
“…These studies show that agricultural programs could be effective platforms to deliver micronutrientfortified products targeted to young children or other household members. Of the six studies that measured child anthropometry (Miller et al, 2014;Rawlins et al, 2014;Olney et al, 2015;Osei et al, 2015Osei et al, , 2017Kumar et al, 2018), however, none found an impact on stunting, with the exception of the livestock study in Nepal that found impacts in Terai, but not in the Hill regions (Miller et al, 2014). Impacts on wasting, or low weight-for-height (WHZ), were reported in four studies, but were generally of small size or only marginally significant (Miller et al, 2014 in one region only; Rawlins et al, 2014;Olney et al, 2015;Kumar et al, 2018).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Livestock-oriented programs typically fall under this category, and have not traditionally included nutrition interventions (such as BCC) even though they may have nutrition goals such as increasing consumption of animalsource foods, improving household dietary diversity and, in some cases, child nutritional status (Ruel et al, 2017). For example, Heifer International's community development program in Nepal provided livestock and training to rural women's self-help groups, intended to promote income generation by building women's social capital (Miller et al, 2014;Darrouzet-Nardi et al, 2016). Miller et al (2014) found that, in the Terai areas where program implementation was stronger, the intervention group had significantly increased income per household member (+6,712 vs +2,589 NPR (Nepalese rupees)), improved sanitation practices, better child weight-for-age (WAZ) and height-for-age z-scores (HAZ), and reduced reported sick days compared with control.…”
Section: Targeting Resource Transfers Through Women's Groupsmentioning
confidence: 99%
“…For example, Heifer International's community development program in Nepal provided livestock and training to rural women's self-help groups, intended to promote income generation by building women's social capital (Miller et al, 2014;Darrouzet-Nardi et al, 2016). Miller et al (2014) found that, in the Terai areas where program implementation was stronger, the intervention group had significantly increased income per household member (+6,712 vs +2,589 NPR (Nepalese rupees)), improved sanitation practices, better child weight-for-age (WAZ) and height-for-age z-scores (HAZ), and reduced reported sick days compared with control. Household health practices improved in the intervention group from baseline, with more households reporting a water tap in the compound (12% to 28%) and a toilet in their home (40% to 70%), and were more likely to treat drinking water (12% vs 5%) and use soap for hand washing.…”
Section: Targeting Resource Transfers Through Women's Groupsmentioning
confidence: 99%